2020
DOI: 10.1021/acsinfecdis.0c00132
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Metal Speciation in Streptococcus sanguinis Establishes SsaACB as Critical for Redox Maintenance

Abstract: Streptococcus sanguinis is an oral commensal bacterium, but it can colonize pre-existing heart valve vegetations if introduced into the bloodstream, leading to infective endocarditis. Loss of Mn-or Fe-cofactored virulence determinants are thought to result in weakening of this bacterium. Indeed, intracellular Mn accumulation mediated by the lipoprotein SsaB, a component of the SsaACB transporter complex, has been shown to promote virulence for endocarditis and O 2 tolerance. To delineate intracellular metal-io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 78 publications
(162 reference statements)
7
24
0
Order By: Relevance
“…This transporter and orthologs in related species have been shown to be important for manganese (Mn) transport and virulence (Colomer-Winter et al, 2018;Crump et al, 2014;Dintilhac et al, 1997;Kehl-Fie et al, 2013). Previous studies utilizing a Δ ssaACB strain of S. sanguinis revealed that this mutant is significantly deficient in cellular Mn levels (Murgas et al, 2020) and virulence in our rabbit model of IE (Baker et al, 2019). These studies also suggested that the reduced virulence of Mn-deficient cells is due to growth arrest in the aerobic, low-Mn environment characteristic of an aortic valve infection, implying the existence of one or more Mn-dependent metabolic pathways that are essential for aerobic growth.…”
Section: Introductionsupporting
confidence: 57%
“…This transporter and orthologs in related species have been shown to be important for manganese (Mn) transport and virulence (Colomer-Winter et al, 2018;Crump et al, 2014;Dintilhac et al, 1997;Kehl-Fie et al, 2013). Previous studies utilizing a Δ ssaACB strain of S. sanguinis revealed that this mutant is significantly deficient in cellular Mn levels (Murgas et al, 2020) and virulence in our rabbit model of IE (Baker et al, 2019). These studies also suggested that the reduced virulence of Mn-deficient cells is due to growth arrest in the aerobic, low-Mn environment characteristic of an aortic valve infection, implying the existence of one or more Mn-dependent metabolic pathways that are essential for aerobic growth.…”
Section: Introductionsupporting
confidence: 57%
“…All plates were incubated for 24 h at 37°C under anaerobic conditions, where atmospheric composition was adjusted using a programmable Anoxomat™ Mark II jar-filling system (AIG, Inc.) and a palladium catalyst was included in the jars. The Δ ssaACB::aphA-3 mutation was nonpolar, as confirmed by complementation (Murgas et al, 2020). All mutants were confirmed to have the expected composition by sequence analysis of the DNA flanking the insertion sites.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 67%
“…1, cellular Zn levels in Δ ssaACB were not significantly altered by EDTA addition, despite the high affinity of this chelator for Zn (Perrin and Dempsey, 1974). Zn level maintenance may be due to the higher levels of Zn than Mn in BHI (1.7 ± 0.02 vs. 0.02 ± 0.003 µg ml -1 , respectively) (Murgas et al, 2020) or the regulation of Zn transporter genes. In S. pneumoniae, transcription of the operon encoding the Zn ABC transporter AdcCBA (Dintilhac and Claverys, 1997) is repressed by a Zndependent, MarR-family regulator called AdcR (Shafeeq et al, 2011;Manzoor et al, 2015).…”
Section: Regulation Of Metal Transport Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work from our lab established that the ABC transporter SsaACB is important for Mn transport and essential for virulence in a rabbit model of IE (Crump et al, 2014;Baker et al, 2019;Murgas et al, 2020). In S. sanguinis, Mn acts as a cofactor for superoxide dismutase (SodA) (Parker and Blake, 1988;Poyart et al, 1988) and the aerobic class 1b ribonucleotide reductase (NrdEF) (Makhlynets et al, 2014;Rhodes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%